Effect of Granulocyte Colony-Stimulating Factor (G-CSF) on Improving Impairment Scale After Acute Spinal Cord Injury: An Individual Participant Data Meta-Analysis - Seyyed Amir Yasin Ahmadi; Mohammad Javad Nourmohammadi; Ahmed Sayahi; Babak Alijani; Shahrokh Yousefzadeh-Chabok; Jafar Rezaian (Iranian Journal of Neurosurgery, 2022)
Background and Aim: The present study was conducted to investigate the effects of granulocyte colony-stimulating factor (G-CSF) after acute spinal cord injury on increasing a grade of improvement entitled American spinal cord injury association impairment scale (AIS) as an individual participant data (IPD) meta-regression analysis of clinical trials. Methods and Materials/Patients: According to our search strategy, four studies were selected. Multilevel ordered logistic regression modeling was used to predict AIS grade with G-CSF administration and time variable (first day and a 3-month follow-up). The IDs of the studies as well as the time series variable were imported to the random part of the model. Odds ratio (OR) and 95% confidence interval (CI) were reported. Results: A total of 277 samples were studied. A fixed effect model was performed at first. Accordingly, using G-CSF was associated with increased AIS grade (lower impairment) (OR=1.503, 95% CI=1.110-2.035) adjusted with time series (OR=1.868, 95% CI=1.378-2.532). In the mixed effect model, G-CSF was again associated with increased AIS grade (OR=1.780, 95% CI=1.301- 2.436) adjusted with time series (OR=2.152, 95% CI=1.406-3.294). Conclusion: The present meta-analysis showed the protective effect of GCS-F observed as an improvement in AIS grade. This protecting effect was further after adjusting the random effects of time series and individual studies. Although multilevel modeling could reduce our limitations, it should be regarded that the number of trials was not enough to establish strong conclusions.